Assessment of the competence in electrocardiographic interpretation among Arabic resident doctors at the emergency medicine and internal medicine departments: A multi-center online cross-sectional study - Rakab, Amine; Swed, Sarya; Alibrahim, Hidar; Bohsas, Haidara; Abouainain, Yasmeen; Abbas, Kirellos Said; Khair Eldien Jabban, Yazan; Sawaf, Bisher; Rageh, Bushra; Alkhawaldeh, Majd; Al-Fayyadh, Israa; Rakab, Mohamad Saad; et al. (Frontiers in Medicine, 2023)
Background: This study aims to assess the electrocardiographic interpretation abilities of resident doctors at internal medicine and emergency medicine departments in eight Arabic countries. Methods: An online cross-sectional study was conducted between October 7, 2022 and October 21, 2022 in eight Arabic countries. The questionnaire consisted of two main sections: the first section included sociodemographic information, while the second section contained 12 clinical case questions of the most severe cardiac abnormalities with their electrocardiography (ECG) recordings. Results: Out of 2,509 responses, 630 were eligible for the data analysis. More than half of the participants were males (52.4%). Internal medicine residents were (n=530, 84.1%), whereas emergency medicine residents were (n=100, 15.9%). Almost participants were in their first or second years of residency (79.8%). Only 36.2% of the inquired resident doctors had attended an ECG course. Most participants, 85.6%, recognized the ECG wave order correctly, and 50.5% of the participants scored above 7.5/10 on the ECG interpretation scale. The proportions of participants who were properly diagnosed with atrial fibrillation, third-degree heart block, and atrial tachycardia were 71.1%, 76.7%, and 56.6%, respectively. No statistically significant difference was defined between the internal and emergency medicine residents regarding their knowledge of ECG interpretation (P value=0.42). However, there was a significant correlation between ECG interpretation and medical residency year (P value<0.001); the fourth-year resident doctors had the highest scores (mean=9.24, SD =1.6). As well, participants in the third and second years of postgraduate medical residency have a probability of adequate knowledge of ECG interpretation more than participants in the first year of residency (OR=2.1, P-value=0.001) and (OR=1.88, P-value=0.002), respectively. Conclusion: According to our research findings, resident doctors in departments of internal medicine and emergency medicine in Arabic nations have adequate ECG interpretation abilities; nevertheless, additional development is required to avoid misconceptions about critical cardiac conditions.